Chemical and Biological properties of compost produced from house solid waste. - Rezan Sabah Ahmed; Sayran Yousif Jalal; Hero Mohhamad Ismael; Yahya Ahmed Shekha (Zanco Journal of Pure and Applied Sciences, 2023)
The primary objective of this research was to investigate the chemical and biological properties of compost produced from different row materials. These materials are solid waste from organic houses, residues from plants, manure from animals, paper and grass. The process of composting to produce mature compost takes 30 days. Nevertheless, compost assessed chemical characteristics included: pH, EC, total organic carbon, total nitrogen, total phosphorous and organic matter. The pH value was near to neutral 7.3. Organic carbon content and organic matter content was 23 and 39.48 respectively. The biological results reveals a total of 22 different species of fungi including: Acremonium, Aspergillus, Cladosporium, Emricella, Eurotium, Fusarium, Geotricum, Humicola, Mucor, Penicillium, Stechybotrys, tetracoccosporium, and Thermomyces, the result showed that the most frequently isolated fungi was Aspergillus spp. (10*103 CFU), especially Asp. niger which was (6*103 CFU), followed by Alternaria spp., which was (4*103 CFU).